Matematyka
stat1x
2017-06-25 08:30:55
Oblicz (zadanie w załączniku)
Odpowiedź
Aga120o
2017-06-25 13:04:13

[latex]frac{sqrt[3]{-9}cdotsqrt[3]{-9}}{sqrt[3]{-3}}-frac{sqrt[3]{24}}{sqrt[3]{-3}} = sqrt[3]{frac{(-9)cdot(-9)}{-3}}-sqrt[3]{frac{24}{-3}}=sqrt[3]{3cdot(-9)}-sqrt[3]{-8}=\\=sqrt[3]{(-3)^{3}}-sqrt[3]{(-2)^{3}} = -3-(-2) = -3 + 2 = -1[/latex]

choim1
2017-06-25 13:05:28

[latex] frac{ sqrt[3]{-9}*sqrt[3]{-9} }{ sqrt[3]{-3} } - frac{ sqrt[3]{24} }{sqrt[3]{-3}} = sqrt[3]{ frac{-9*(-9)}{-3} } - sqrt[3]{ frac{24}{-3} } = sqrt[3]{-27} - sqrt[3]{ -8}=-3-(-2)= \ \ oxed{=-1} \ \ \ \ \ "Non nobis Domine, non nobis, sed Nomine tuo da gloriam." \ \ \ \ underline{underline{Pozdrawiam M.Y.}}[/latex]

Dodaj swoją odpowiedź